Legal Integration of Contract Law and Accounting Standards: Auditors’ Role in Ensuring Certainty and Risk Prevention - Soesetiawan, Indra (LifeSciFi, 2026)
The increasing reliance on accounting standards as regulatory instruments has expanded the legal responsibilities of business actors and independent auditors. PSAK 115 adopts a contract-based approach to revenue recognition, making contractual clarity a prerequisite for regulatory compliance. This article examines the integration between contract law principles and accounting standards from a normative legal perspective, emphasizing the professional responsibility of independent auditors to understand business law, civil law, and potential criminal law implications. Using a normative juridical method with statutory and conceptual approaches, this study finds that deficiencies in contract design not only impair revenue recognition under PSAK 115 but also expose companies and auditors to significant legal risks. The article argues that legal certainty in financial reporting requires synergy between contract law and accounting regulation, supported by auditors who possess adequate legal awareness. Such integration is essential to minimize disputes, prevent allegations of misrepresentation or fraud, and strengthen legal compliance in corporate governance.